MSME Sustainability as the Key to Sustainability: Role and Contribution of MSMEs to Sustainability with a Bibliometric Approach and Literature Review - Gunawan, William Ben (Equator Journal of Management and Entrepreneurship (EJME), 2025)
This study explores the contribution of micro, small, and medium enterprises (MSMEs) to sustainability through bibliometric analysis and a literature review, focusing on their role in supporting economic, environmental, and social sustainability in Indonesia. A bibliometric approach was employed to evaluate research trends, publication patterns, and the distribution of studies by country in literature published between 2019 and 2024. Literature searches were conducted in the Scopus database using the keywords "SME*" or "MSME*" and "sustainability," yielding 962 relevant documents. Analysis using VOSviewer identified frequently recurring keywords and mapped research clusters related to the contributions of MSMEs. The key findings indicate that MSMEs play a crucial role in achieving sustainability goals, despite facing challenges such as limited resources and restricted access to technology. Through innovation, collaboration, and appropriate policy support, MSMEs have the potential to overcome these barriers. The implications of this study highlight the importance of a multidimensional approach involving all stakeholders, including government, the private sector, and local communities. Strategic efforts such as adopting sustainable business practices, leveraging modern technologies, and enhancing capacity through training are essential to strengthening MSMEs' contributions to sustainability. The study concludes that MSMEs' role is not only significant for the economy but also has broad implications for environmental and social sustainability, underscoring the need for comprehensive support to empower MSMEs in addressing global challenges.